ДОСЛІДЖЕННЯ АЛГОРИТМА ІМПЕДАНСНО-ДИФЕРЕНЦІАЛЬНОГО ЗАХИСТУ ЯК ЛОКАТОРA ПОШКОДЖЕНЬ ДЛЯ ЛІНІЇ ЕЛЕКТРОПЕРЕДАЧІ - Герлендер, Ю.; Ижиковски, Я.; Брусилович, Б. (Інститут електродинаміки НАН України, Київ, 2020)
This paper deals with an analysis of impedance-differential protection algorithm applied to locate faults on a double-circuit transmission line. In particular, the study of fault location accuracy for the case of using the relation between currents for negative-sequence not for zero-sequence, as it was presented so far, is provided. It results from the well-known fact that zero-sequence impedances are in practice considered as quite unreliable data. Therefore, one has to limit usage of zero-sequence impedance parameters as much as possible. Such approach was applied in this paper and therefore the use of the additional relation of currents for negative-sequence is under investigation. The fault signals from ATP-EMTP simulation on the sample double-circuit transmission line was applied for evaluating the fault location accuracy. References 8, figures 4, table 1.